Method for preparing battery-grade lithium fluoride from industrial lithium carbonate
Through the combination technology of phosphoric acid chelating resin and cyclic ether extractant, the problem of difficult removal of impurity ions in battery-grade lithium carbonate is solved, and the preparation of high-purity lithium fluoride is realized, which reduces production costs and meets new energy sources. High standards of the industry.
Patent Information
- Application Number
- CN202411439104.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-31
AI Technical Summary
The existing technology is difficult to effectively reduce the impurity content of sodium ions, potassium ions, calcium ions and magnesium ions in battery-grade lithium carbonate, resulting in poor quality of battery-grade lithium fluoride, which cannot meet the high standards requirements of the new energy industry, and production Higher cost.
Phosphoric acid chelating resin is used for ion exchange, combined with cyclic ether as extraction agent, selective complexation and adsorption of sodium and potassium ions to reduce their content, and the purity of lithium fluoride is improved through thermal de-crystallization and hydrogenation treatment.
Successfully reduced the content of sodium and potassium impurities to 5 ppm, and the content of calcium, magnesium and heavy metal impurities to 1 ppm, significantly reducing production costs, improving the quality of lithium fluoride, meeting the market's requirements for high purity, and not Increased yields with increased process costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium fluoride preparation, and specifically relates to a technical process for purifying industrial-grade lithium carbonate to prepare battery-grade lithium fluoride. Background Art
[0002] As a precursor of lithium hexafluorophosphate, a lithium salt used in lithium battery electrolytes, the demand for battery-grade lithium fluoride is growing rapidly with the booming development of the current new energy industry. In recent years, more and more new energy companies have begun to deploy the production of battery-grade lithium fluoride. With the rapid expansion of market capacity, the industrial benefits of using battery-grade lithium carbonate as a raw material to prepare battery-grade lithium fluoride have declined significantly, and the production cost of the process needs to be further reduced. The cost of battery-grade lithium carbonate on the raw material side accounts for more than 80% of the total cost of battery-grade lithium fluoride raw materials. Replacing battery-grade lithium carbonate raw materials with lower-cost industrial lithium carbonate can significantly reduce production costs.
[0003] However, industrial lithium carbonate raw materials with poorer quality are used, in which the content of sodium ions, potassium ions, calcium ions, and magnesium ions is significantly increased. It is difficult to reduce the above-mentioned metal ion impurities to less than 10 ppm using the traditional electrocarbon secondary hydrogenation process, and it is necessary to introduce a method for removing sodium, potassium, calcium, and magnesium impurity ions. The present invention introduces a chelating resin, which has a good adsorption effect on calcium, magnesium, and heavy metal ions, and reduces the content of calcium, magnesium, and heavy metal impurity ions to about 1 ppm. For the sodium ions in the industrial lithium carbonate raw materials that are more difficult to remove with a content of more than 2000 ppm, the present invention uses a cyclic ether that can selectively complex sodium ions as a complexing agent, and then reduces the sodium ion content to less than 10 ppm by extraction, and the complexing agent also has a certain complexing effect on potassium ions. Finally, the method used in the present invention can reduce the content of sodium and potassium impurities to 5 ppm, and the content of calcium, magnesium, and other heavy metal impurities to 1 ppm. Compared with general industrial lithium carbonate, the quality of lithium fluoride prepared is better, and it can better meet the high standard requirements of the liquid lithium hexafluorophosphate process for metal impurities in the raw material lithium fluoride that has appeared in the market in the past two years. In summary, the present invention can achieve the removal of sodium and potassium by using a relatively small amount of complexing agent. The new chelating resin used has strong adsorption capacity for calcium and magnesium and can be repeatedly used for a long time. Without significantly increasing the process cost, the cost of raw materials required for the production of lithium fluoride is greatly reduced, and the cost reduction and efficiency improvement are obvious, which has practical significance for industrialization. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a method for preparing battery-grade lithium fluoride from industrial lithium carbonate. The technical solution of the present invention is as follows: A method for preparing battery-grade lithium fluoride from industrial lithium carbonate comprises the following steps: (1) industrial lithium carbonate and water are mixed and stirred in a ratio of 1:(15-25), and carbon dioxide is introduced into the pulping solution at a flow rate of 0.3-10.0 L / min at a temperature of 0-20°C for reaction. After reacting for 1-6 hours, a lithium bicarbonate solution is obtained, which is then filtered to obtain a lithium bicarbonate filtrate; the stirring speed is 300-700 r / min, the purity of industrial lithium carbonate is in the range of 98.5-99.5%, the conductivity of ultrapure water is ≤0.5 us / cm, and the purity of carbon dioxide is 99.5%; (2) The lithium bicarbonate filtrate obtained above is passed through an ion exchange column to obtain a lithium bicarbonate solution with low content of calcium ions, magnesium ions and heavy metal ions. The ion exchange resin column is filled with aminophosphoric acid chelating resin material, and the resin model adopts LSC-850, LSC-500, and LSC-100 series resins of Xi'an Lanxiao Technology. The flow rate of the lithium bicarbonate filtrate through the resin column is 1-12 BV / h. This series of resins is a chelating resin specially selected for removing calcium ions, magnesium ions, and other heavy metal ions in water solutions, especially for lithium bicarbonate solutions. It has a very obvious effect on reducing calcium ions and magnesium ions; (3) extracting the lithium bicarbonate solution, first adding an extractant to the lithium bicarbonate solution, stirring and mixing for 10-60 min, then adding an organic phase solvent, the volume ratio of the organic phase to the aqueous phase is 1: (0.8-3.0), the pH range of the aqueous phase is 8.0-12.0, and the stirring and mixing is continued for 10-60 min, and then standing for stratification for 3-10 min, and separating to obtain a lithium bicarbonate solution with less sodium ion and potassium ion content in the lower layer; The crown ether or its derivative is selected from any one of 15-crown-5, 15-crown-5-R1, benzo-15-crown-5, benzo-15-crown-5-R2, dibenzo-15-crown-5, dibenzo-15-crown-5-R3, 18-crown-6, 18-crown-6-R1, benzo-18-crown-6, benzo-18-crown-6-R2, dibenzo-18-crown-6, and dibenzo-18-crown-6-R3, and R1, R2, and R3 are alkane chains with 0-3 carbon atoms containing amino, hydroxyl, carboxyl, formyl, and nitro groups.
[0005] The cyclic ether extractant can also be 4,7,13,16,21-pentaoxo-1,10-diazabicyclo[8.8.5]tricosane cryptand 2,2,1 or its derivative cryptand 2,2,1-R4, wherein R1, R2 and R3 are alkane chains with 0-3 carbon atoms containing amino, hydroxyl, carboxyl, formyl or nitro groups.
[0006] The concentration range of the extractant is 0.01 g / L-5 g / L, the organic phase is selected from one of the organic solvents such as ethyl acetate, acetone, benzene, dichloromethane, chloroform, etc., the extraction is carried out at a temperature of 0-40°C, and the stirring rate is 200-500 r / min; In some embodiments, the extractant includes crown ether A, crown ether B, crown ether C, and cryptand D, and the structural formula thereof is as follows:
[0007] Crown ether A Crown ether B Crown ether C Cryptide ether D The R1, R2, R3 and R4 are alkane chains with 0-3 carbon atoms and containing amino, hydroxyl, carboxyl, formyl and nitro groups.
[0008] (4) The extracted lithium bicarbonate solution is heated to 70-100° C. and then pyrolyzed and crystallized at a stirring rate of 200-500 r / min. After reacting for 1.0-4.0 h, the solution is filtered to obtain solid lithium carbonate and pyrolysis mother liquor, and the pyrolysis mother liquor is stored and recycled as the next batch of industrial-grade lithium carbonate mother liquor; (5) The industrial lithium carbonate solid obtained above is mixed with ultrapure water in a ratio of 1:(10-20), the stirring rate is 200-500 r / min, carbon dioxide (purity 99.5%) is introduced, the ventilation rate is 0.3-10 L / min, the reaction time is 30-120 min, the hydrogenation temperature is 0-20° C., and the lithium bicarbonate solution is obtained by hydrogenation; (6) Add 50% by mass of hydrofluoric acid (industrial grade) to the above lithium bicarbonate solution, the feed ratio of hydrofluoric acid to lithium bicarbonate solution is 1:(15-30), stop adding hydrofluoric acid when the pH of the solution reaches 5, the reaction temperature is 0-30°C, the stirring rate is 200-500 r / min, and the reaction time is 0.5-2 h to obtain a lithium fluoride suspension. Then filter, and dry the obtained lithium fluoride solid at 70-230°C for 8-15 h.
[0009] Preferably, the flow rate of the lithium bicarbonate solution through the resin column in step (2) is 1-3 BV / h; Preferably, the cyclic ether in step (3) is selected from 15-crown-5 and its derivatives, benzo-15-crown-5 and its derivatives, dibenzo-15-crown-5 and its derivatives, cryptand 2,2,1 and its derivatives, all of which have a 15-membered ring containing an ether group, the size of which can just match the size of the sodium ion, and after forming a complex with the sodium ion, it is more stable, and at the same time has a certain complexing ability for potassium ions. In addition, cryptand 2,2,1 and its derivatives also form a three-dimensional structure similar to a cage, which effectively wraps the sodium ion in the middle of the "cage", and the complexing effect is better than that of 15-crown-5 derivatives, but the industrial production cost of 15-crown-5 derivatives is lower.
[0010] Further preferably, in step (3), the extractant is selected from the crown ether A and cryptand D of the above-mentioned cyclic ethers. Since crown ether B and crown ether C have benzene rings, the benzene rings will form p-π conjugation with the coordinating atoms of the crown ether, thereby reducing the electron cloud density of the coordinating atoms of the crown ether and reducing the coordination effect of the crown ether, and the ability to complex sodium ions and potassium ions will decrease; More preferably, in step (3), the extractant is selected from a crown ether or a cryptand having a carbon chain with 0-3 carbon atoms or an alkane chain with 0-3 carbon atoms and a hydroxyl group or an amino group. The hydroxyl group, the amino group, and the saturated alkane group are electron-repelling groups, which increase the charge density around the coordinating atoms of the cyclic ether, thereby enhancing its coordination ability and making it more stable after complexing with sodium ions and potassium ions, thereby significantly reducing the sodium ion and potassium ion content in the lithium bicarbonate solution.
[0011] Examples of the structures of crown ethers or cryptands of carbon chains with 0-3 carbon atoms or alkane chains with 0-3 carbon atoms and hydroxyl or amino groups are as follows, but are not limited to the following structures:
[0012] 2,2-Dimethyl-15-crown-52-hydroxymethyl-15-crown-52-aminomethyl-15-crown-55-methyl-cryptand 2,2,1 Preferably, in step (4), the pyrolysis temperature of the lithium bicarbonate solution is 80-90° C., the pyrolysis time is 1.5-2.5 h, and the stirring rate is 300-500 r / min; Preferably, in step (5), lithium carbonate and ultrapure water are mixed at a ratio of 1:(15-20), with a stirring rate of 300-500 r / min, a ventilation rate of 1.5-4.0 L / min, a reaction time of 60-120 min, and a hydrogenation temperature of 0-10°C.
[0013] Preferably, in step (6), the feed ratio of hydrofluoric acid to lithium bicarbonate solution is 1:(20-30), the reaction temperature is 0-20° C., the stirring rate is 300-500 r / min, and the reaction time is 0.5-1.0 h.
[0014] Preferably, the solid lithium fluoride obtained by filtration in step (6) is dried at a temperature of 80-180° C. for 8-12 h to finally obtain battery-grade lithium fluoride.
[0015] Compared with the prior art, the technical solution provided by the present invention has the following technical advantages: 1. The raw material used in the present invention is a low-priced industrial lithium carbonate raw material with a purity of 98.5-99.5% and a sodium ion, potassium ion and other impurity content higher than 500 ppm; 2. The aminophosphoric acid chelating resin materials used, LSC-850, LSC-500, LSC-100 series resins are used to selectively adsorb calcium ions, magnesium ions, and other heavy metal ions. After resin adsorption, the calcium ions, magnesium ions, and heavy metal ions can be reduced to less than 1ppm; 3. The present invention creatively combines the resin adsorption method with the extraction method, and uses cyclic ethers as extractants. Cyclic ethers such as 15-crown-5 derivatives and cryptand derivatives can selectively complex sodium ions and partially complex potassium ions, but have weak complexing ability for lithium ions, and will not affect the final lithium yield while removing sodium ions. This method is used to specifically solve the problem that when the sodium ion content in the raw material industrial lithium carbonate is high (ranging from 1500-2500 ppm), traditional lithium carbonate pulping and washing or lithium fluoride pulping and washing are difficult to remove sodium ions to less than 10 ppm. Ultimately, this method can reduce the sodium ion and potassium ion content to less than 5 ppm, which is better than the 10 ppm content required by the standard. DETAILED DESCRIPTION
[0016] In order to fully demonstrate the effect of the present invention, the present invention is described in detail through the following specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0017] Example 1 Weigh 100 g of industrial lithium carbonate (purity 98.5%-99%) and 1600 g of ultrapure water, and beat at a stirring speed of 400 r / min. Introduce carbon dioxide into the beaten solution, control the carbon dioxide gas flow rate to 0.3 L / min, the reaction temperature to 7°C, and react for 2.5 h to obtain a lithium bicarbonate suspension, which is then filtered to obtain a lithium bicarbonate filtrate. The above filtrate is passed through an ion exchange column filled with LSC-850 resin, with a resin flow rate of 2.0 BV / h. Add 0.5 g of 15-crown ether-5 to the lithium bicarbonate solution after the resin, stir for 20 min, then add 600 ml of dichloromethane, stir for 20 min, and then stand for 5 min. After stratification, separate the lower layer of lithium bicarbonate solution. Heat and stir at 90°C for 2.5 h to obtain a lithium carbonate suspension, which is filtered to obtain a purified lithium carbonate solid. Lithium carbonate solid was mixed with ultrapure water at a ratio of 1:16, stirred at 400 r / min, and carbon dioxide was introduced at a rate of 0.3 L / min. The reaction time and temperature were controlled to be 2.0 h and 7°C, respectively, to obtain a lithium bicarbonate clear solution. Then hydrofluoric acid was added to the clear solution while stirring until the pH was below 5, and the reaction temperature was controlled to be 15°C. The reaction ended after 1.0 h, and then filtered and dried at 120°C for 8.0 h to obtain battery-grade lithium fluoride with a purity of 99.99%. The pyrolysis mother liquor was reused, and the experimental yield was recorded.
[0018] Example 2 The extractant 15-crown ether-5 in Example 1 was replaced by 2,2-dimethyl-15-crown ether-5, and other conditions remained the same to prepare battery-grade lithium fluoride with a purity of 99.99%, and the pyrolysis mother liquor was reused, and the experimental yield was recorded.
[0019] Example 3 The extractant 15-crown ether-5 in Example 1 was replaced by 2-hydroxymethyl-15-crown ether-5, and other conditions remained the same to prepare battery-grade lithium fluoride with a purity of 99.99%, and the pyrolysis mother liquor was reused, and the experimental yield was recorded.
[0020] Example 4 The extractant 15-crown ether-5 in Example 1 was replaced by 2-aminomethyl-15-crown ether-5, and other conditions remained the same to prepare battery-grade lithium fluoride with a purity of 99.99%, and the pyrolysis mother liquor was reused, and the experimental yield was recorded.
[0021] Example 5 The extractant 15-crown-5 in Example 1 was replaced by cryptand 2,2,1, and other conditions were kept the same to prepare battery-grade lithium fluoride with a purity of 99.99%. The pyrolysis mother liquor was reused and the experimental yield was recorded.
[0022] Example 6 The extractant 15-crown-5 in Example 1 was replaced by 5-methyl-cryptand 2,2,1, and other conditions were kept the same to prepare battery-grade lithium fluoride with a purity of 99.99%, and the pyrolysis mother liquor was reused, and the experimental yield was recorded.
[0023] Comparative Example 1 The lithium bicarbonate filtrate obtained by the primary hydrogenation and filtration in Example 1 was directly subjected to pyrolysis, secondary hydrogenation, and hydrofluoric acid addition reaction without passing through LSC-850 resin or adding an extractant to prepare lithium fluoride. Except for not passing through the resin and not extracting, other conditions were consistent with Example 1, and the pyrolysis mother liquor was reused, and the experimental yield was recorded.
[0024] Comparative Example 2 The lithium bicarbonate filtrate obtained by the primary hydrogenation and filtration in Example 1 was passed through LSC-850 resin, and then directly subjected to pyrolysis, secondary hydrogenation, and hydrofluoric acid addition reaction without adding an extractant to prepare lithium fluoride. Except for not performing the extraction operation, other conditions were consistent with those in Example 1, and the pyrolysis mother liquor was reused, and the experimental yield was recorded.
[0025] The contents of cationic impurities and anionic impurities in the lithium fluoride prepared in Examples 1-6 and Comparative Examples 1-2 were tested, as shown in Table 1.
[0026] Table 1 Impurity content in lithium fluoride prepared in Examples 1-6 and Comparative Examples 1-2 Specific embodiments purity / % <![CDATA[Cl - ppm]]> <![CDATA[SO4 2- / ppm]]> Na / ppm K / ppm Mg / ppm Ca / ppm Fe / ppm Al / ppm Ni / ppm Cu / ppm Yield / % <![CDATA[Industrial LiCO3 Standard]]> 99.0 200 3500 1500 1000 150 400 100 100 50 50 / <![CDATA[Content of raw material LiCO3]]> 99.0 52.4 1812 2474.5 592.6 35.7 299.1 25.4 10.1 7.8 4.2 / LiF Standard 99.95 20 20 10 10 10 10 10 10 5 5 / Example 1 99.99 2.51 10.97 3.02 1.58 0.67 0.90 0.77 0.26 N 0.05 91.7 Example 2 99.99 0.75 9.10 2.28 1.09 1.03 0.55 0.29 N N 0.13 92.8 Example 3 99.99 2.46 9.99 2.79 1.12 0.40 0.62 0.47 0.31 N N 92.2 Example 4 99.99 3.57 8.24 3.67 2.50 N 0.31 N 0.24 N 0.08 91.6 Example 5 99.99 2.02 10.66 1.08 0.78 0.92 0.58 0.15 N 0.17 N 94.8 Example 6 99.99 2.73 8.19 1.49 1.02 1.11 0.83 0.31 0.13 N 0.06 95.5 Comparative Example 1 99.95 5.97 11.14 182.13 23.09 12.86 69.18 2.55 1.41 0.69 0.44 87.2 Comparative Example 2 99.95 4.05 10.26 159.07 19.20 1.73 2.49 1.96 1.89 0.34 0.37 85.6 According to the lithium fluoride test results of the above-mentioned Examples 1-6, after the lithium bicarbonate solution is first passed through the LSC-850 resin material, compared with the comparative example 1 without the resin column, the impurity content of calcium ions, magnesium ions, and heavy metal ions in the lithium bicarbonate solution after passing through the LSC-850 resin column is basically less than 1 ppm, and the content of calcium ions and magnesium ions is much lower than the data results of the comparative example 1 without the LSC-850 resin. Compared with the comparative example 2 without the addition of the extractant, the lithium fluoride test results of Examples 1-6 show that the impurity content of sodium ions and potassium ions in Examples 1-6 can be reduced to less than 5 ppm, while the sodium ion content in the comparative example 1-6 without the addition of the extractant specifically for removing sodium ions is far more than the 10 ppm specified in the standard. And by comparing the experimental yield results of Examples 1-6 and Comparative Example 1-2, it can be seen that the addition of cyclic ether extractants does not lead to a decrease in the yield of battery-grade lithium fluoride. The above embodiments and comparative examples illustrate that the combination of resin and extractant can effectively remove sodium ion, potassium ion, calcium ion and magnesium ion impurities, and these four impurity ions are usually high in raw material lithium carbonate and difficult to remove from product battery-grade lithium fluoride. At the same time, when the raw material industrial lithium carbonate has high sodium ion, potassium ion and calcium ion content, the method still has a good impurity removal effect when the quality of lithium carbonate is 98.5%. The quality of battery-grade lithium fluoride prepared by this method is even better than that of lithium fluoride prepared by traditional methods using better quality raw material battery-grade lithium carbonate.
[0027] In addition, by comparing the yields of Examples 1-6 and Comparative Examples 1-2, the addition of a cyclic ether extractant not only improves the quality of the product over that of lithium fluoride prepared without the addition of an extractant, but also improves the yield, especially in Examples 5 and 6 using cryptands as extractants. The reason is that cryptands have stronger selective complexing properties for sodium ions and potassium ions, and basically do not complex lithium ions, resulting in very little lithium loss, and the final prepared lithium fluoride has a higher yield.
[0028] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing battery-grade lithium fluoride from industrial lithium carbonate, characterized in that: include: (1) industrial lithium carbonate and water are mixed, stirred and slurried, and carbon dioxide is introduced into the mixture under stirring to obtain lithium bicarbonate filtrate; (2) purifying the lithium bicarbonate filtrate obtained above by ion exchange resin to obtain a sub-pure lithium bicarbonate solution; (3) adding an extractant to a semi-pure lithium bicarbonate solution, mixing thoroughly, then adding an organic solvent, and then mixing thoroughly for a certain period of time, standing to separate the layers, and separating to obtain a purified lithium bicarbonate solution; (4) heating the purified lithium bicarbonate solution to pyrolyze it, crystallizing lithium carbonate precipitate, and filtering to obtain wet lithium carbonate; (5) mixing the wet lithium carbonate material with water and introducing carbon dioxide to generate a lithium bicarbonate solution; (6) Add hydrofluoric acid solution to the above pure lithium bicarbonate solution to obtain battery-grade lithium fluoride.
2. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 1, characterized in that: The purity of the industrial lithium carbonate in step (1) is in the range of 98.5-99.5%.
3. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 1, characterized in that: In step (2), the ion exchange resin is selected from aminophosphoric acid chelating resin material, and the resin model used is LSC-850, LSC-500, LSC-100, etc.
4. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 1, characterized in that: The extractant in step (3) is a cyclic ether extractant, and the cyclic ether extractant is selected from crown ethers and their derivatives. The crown ether or its derivative is selected from any one of 15-crown-5, 15-crown-5-R1, benzo-15-crown-5, benzo-15-crown-5-R2, dibenzo-15-crown-5, dibenzo-15-crown-5-R3, 18-crown-6, 18-crown-6-R1, benzo-18-crown-6, benzo-18-crown-6-R2, dibenzo-18-crown-6, and dibenzo-18-crown-6-R3, and R1, R2, and R3 are alkane chains with 0-3 carbon atoms containing amino, hydroxyl, carboxyl, formyl, and nitro groups.
5. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 5, characterized in that: The cyclic ether extractant can also be 4,7,13,16,21-pentaoxo-1,10-diazabicyclo[8.8.5]tricosane cryptand 2,2,1 or its derivative cryptand 2,2,1-R4, wherein R1, R2 and R3 are alkane chains with 0-3 carbon atoms containing amino, hydroxyl, carboxyl, formyl or nitro groups.
6. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 5 or 6, characterized in that: The concentration range of the extractant is 0.01 g / L-5 g / L, the aqueous phase is a lithium bicarbonate solution that has passed through a resin column, the organic phase is selected from any one of ethyl acetate, acetone, benzene, dichloromethane, and chloroform, the volume ratio of the organic phase to the aqueous phase is 1:(0.8-3.0), the pH range of the aqueous phase is 8.0-12.0, and the extraction is carried out at a temperature of 0-40°C.
7. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 1, characterized in that: In step (4), the reaction temperature is 75-100° C., the reaction time is 1.0-4.0 h, and the stirring rate is 200-500 r / min.
8. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 1, characterized in that: The lithium carbonate and ultrapure water in step (5) are mixed in a ratio of 1: (10-20), carbon dioxide is introduced, the ventilation rate is 0.3-10 L / min, the stirring time is 30-120 min, and the temperature of the secondary hydrogenation is 0-20°C.
9. The method for preparing battery-grade lithium fluoride from industrial lithium carbonate according to claim 1, characterized in that: In step (6), 50% by mass of hydrofluoric acid is added to the hydrogenated lithium bicarbonate solution, the feed ratio of hydrofluoric acid to lithium bicarbonate solution is in the range of 1:(15-30), the reaction time is 0.5-2 h, and the reaction temperature is 0-30°C.
